Mapping out‐ argument structure. (13th September 2022) - Ahn, Byron
Abstract: This article explores a phenomenon of English in which out‐ combines with a predicate to form a complex predicate (e.g., outsing, outdo, outrun, outsmart, …), here called " out ‐pred ." A thorough investigation uncovers several new generalizations, which can be summarized as follows. (i) Out ‐pred formation is productive and syntactic, building upon the structure for the pred . (ii) Out‐ is the core of the out ‐pred clause's extended verbal projection. These findings are derived via an analysis in which out‐ merges with the pred before any argument(s) can merge. This analysis is then further supported by exploring domains in which out ‐pred is unavailable; though these are seemingly unrelated, they share deep derivational properties that are incompatible with the derivation of out ‐pred . The findings of this article have implications for the syntactic representation of argument structure more generally, supporting analyses where all arguments of a verb are syntactically severed from it.